Are body mass index and the systemic immune-inflammation index risk factors for carpal tunnel syndrome? - Karacan Gölen, Meltem; Yılmaz Okuyan, Dilek (The European Research Journal, 2023)
Objectives: Carpal tunnel syndrome (CTS) is the most common entrapment neuropathy of the upper extremity that affects activities of daily living. In our study, we aimed to reveal the relationship between CTS and BMI, and to evaluate symptom severity and functionality in these patients by using the Boston CTS questionnaire. Methods: In this study, 300 patients with CTS and 100 healthy individuals without CTS whose EMG was performed in our neurology clinic electrophysiology laboratory between June 2021 and December 2021, were included. BMI, SII index, and Boston CTS questionnaire findings were compared between patients diagnosed as having mild, moderate, and severe CTS (according to electrophysiologic evaluations) and a control group consisting of healthy individuals. Results: In our study, a statistically significant difference was observed between the CTS and control groups in terms of mean age (p < 0.001). When the increased BMI and SII parameters were compared, a statistically significant difference was observed between the control and CTS groups (p < 0.001 for both). In the multivariate logistic regression analysis, it was observed that the risk of CTS increased 1.566 times as BMI increased, and the risk of CTS increased 1.005 times as the SII index increased (p < 0.001 for both). Conclusions: We observed that increased BMI and advanced age were risk factors for CTS. In our study, in which the relationship between the SII index and CTS was evaluated for the first time, according to our findings, inflammation was thought to play a role in the pathophysiology of CTS.